The effects of growing in a closed sheltered environment on the psychological and social and physical aspects - salah ben khalifah, Ghadah (Journal of Social Sciences and Humanities, 2024)
The environment that a child grow in is the basis for the formation of their personality, and this research examines the long-term effects of closed sheltering and isolation form their external environment and the results change many aspects of their life, therefore this research aims to define the social, psychological and physical risks of growing in closed environment, by using the descriptive approach to achieve the following results: - All aspects of life are adversely affected when children arise in closed environments. the closed environment is defined as: unjust control of all the situations to which a child is exposed and deprive them of all the attitudes and information they may see, such control may be exercised in extreme unjust fear for the child safety, or it may be an abusive tactic to diminish their knowledge so remain unnaturally needy for there parents until advanced stages of their life. this leads to negative effects on their life such as problem with intellectual maturity and problems with dealing with their peers and making important chooses independently, which reinforce their role of needing other people to depend on like there parents or any other person beside their self, resulting in a financial losses because of the individual inability to evaluate and chose good opportunities for their self or cooperating with others to increase there chance to get a promotion or advancing in their personal life because of their psychological problems that complicates developing a meaningful relationship in their life . and the research conclude that people lives are greatly affected by the environment they grow in, and the parenting styles applied to them. and these negative ways of raising children should be avoided.